2020
DOI: 10.1101/2020.08.11.247080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The chromatin remodeler ISWI acts duringDrosophiladevelopment to regulate adult sleep

Abstract: Sleep disruptions are among the most commonly-reported symptoms across neurodevelopmental disorders (NDDs), but mechanisms linking brain development to normal sleep are largely unknown. From a Drosophila screen of human NDD-associated risk genes, we identified the chromatin remodeler Imitation SWItch/SNF (ISWI) to be required for adult fly sleep. Loss of ISWI also results in disrupted circadian rhythms, memory, and social behavior, but ISWI acts in different cells and during distinct developmental times to aff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 75 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…4, C to E). Consistent with these findings, Gong et al (47) reported that Iswi knockdown in flies results in mushroom body morphologic abnormalities, as well as disrupted sleep, circadian rhythmicity, memory, and social behaviors, suggesting that Iswi is required during development for numerous adult behaviors.…”
Section: Smarca5's Ortholog Iswi Plays a Key Role In Drosophila Larva...mentioning
confidence: 66%
See 1 more Smart Citation
“…4, C to E). Consistent with these findings, Gong et al (47) reported that Iswi knockdown in flies results in mushroom body morphologic abnormalities, as well as disrupted sleep, circadian rhythmicity, memory, and social behaviors, suggesting that Iswi is required during development for numerous adult behaviors.…”
Section: Smarca5's Ortholog Iswi Plays a Key Role In Drosophila Larva...mentioning
confidence: 66%
“…Apart from its previously reported function in cell proliferation/stem cell self-renewal (59) and hence smaller head/ microcephaly, we identified its requirement in postmitotic neurons. Specifically, we found that Iswi LoF leads to defects in sensory neuron dendrite tiling and mushroom body development, highlighting its underappreciated role in neural circuit assembly (47). This likely contributes to the behavioral deficits such as impaired locomotion in the Iswi knockdown flies and intellectual disability, hypotonia, and speech delay in patients.…”
Section: Discussionmentioning
confidence: 82%
“…Apart from its previously reported function in cell proliferation/stem cell self-renewal ( 57 ) and hence smaller head/microcephaly, we identified its requirement in post-mitotic neurons. Specifically, we found that Iswi LoF leads to defects in sensory neuron dendrite tiling and mushroom body development, highlighting its underappreciated role in neural circuit assembly ( 46 ). This likely contributes to the behavioral deficits such as impaired locomotion in the Iswi knockdown flies, and intellectual disability, hypotonia and speech delay in patients.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with these findings, Gong et al . reported that Iswi knockdown in flies results in mushroom body morphologic abnormalities, as well as disrupted sleep, circadian rhythmicity, memory, and social behaviors, suggesting that Iswi is required during development for numerous adult behaviors ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation